INFLUENCE OF A MEDIUM OF PROPAGATION OF HYDROACOUSTIC WAVES ON SPECTRAL AND TEMPORAL STRUCTURES OF RECEIVED SIGNAL - S. R. Heister; T. T. Tran (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Sonar path structure is considered. Frequency dependence of attenuation of acoustic waves propagating in water and its influence on spectral and temporal structures of reflected signals are considered. The results of the basic laws of changes research in temporal and spectral structure of acoustic signal due to propagation in water are represented.